The Effect of Deceptive Marketing Communication on the Brand Equity of Private Higher Education Institutions (PHEIs) in the Northwest and Southwest Regions of Cameroon - Joyvice, Chofor; Atemnkeng, Johannes Tabi; Sama, Molem Christopher; Agbor, MBU Sunday; Buwah, NEBA Noela (International Journal of Social and Administrative Sciences, 2019)
The problem of falling educational standards in Cameroon has been posed severally from a purely educationist perspective. This study however goes from the premise that the liberalization of the Higher Educational Sector in the early 90s ushered in questionable capitalistic business practices by promoters of PHEIs in a bid to uphold their economic bottom lines as they would in any classical sector. This paper examines an extreme unethical mercantilist practice of deceptive marketing communication and its consequences on the brand equity of PHEIs in the Northwest and Southwest Regions of Cameroon. The study is cross-sectional with an exploratory approach. The study largely exploits primary data from alumni of fifteen (15) PHEIs. To mitigate for circumstantial time-bias in predictors, the researchers adopted stratified purposive and exponential non-discriminative snowball sampling. Six hundred (600) questionnaires were issued through the targeted population. For analysis, a Logit Model was applied and the simplified parameters for the various were obtained with the aid of the SPSS 16.0 software. The findings revealed a strong association between deceptive marketing communication and brand equity as it observed that, X2 (5,600) = 139.3 and highly significant (p-value of 0.0001). This was further confirmed by an insignificant Hosmer and Lemeshow Test statistic of 11.7 with a probability value of 0.165. The researchers recommend a review of regulations governing the Private Higher Education sector in Cameroon in terms of mentorship by state universities such that mentorship responsibilities include general operational and marketing supervision and not just pure academic supervision.